Early Numeracy and Literacy Skills Among Monolingual and Bilingual Kindergarten Children - Bar, Liat; Shaul, Shelley (Frontiers in Psychology, 2021)
Early numeracy and literacy skills are all the knowledge that children acquire spontaneously and independently before entering school and beginning formal learning (Li, Legault & Litcofsky, 2014). This knowledge is essential and forms the basis for the acquisition of reading and arithmetic in school (Li, Legault & Litcofsky 2014; Méndez, Crais & Kainz, 2018). A bilingual child is a child who is fluent in two languages, as opposed to a monolingual child who is exposed to only one language (McCardle & Hoff, 2006). Bilingualism has been found to affect verbal and mathematical abilities in children, but only a few studies have focused on the early numeracy and literacy skills of preschoolers. This study examined the connection between early numeracy and literacy skills and among monolingual children as compared to bilingual children in preschool. A total of 302 children 5-6 years old were recruited from 74 kindergartens. Participants were divided into two groups: 151 monolingual children who spoke and were exposed to only one language (Hebrew), and 151 bilingual children who spoke and were exposed to two languages (the bilingual children spoke different languages). Monolingual children performed better than the bilingual children in most of the literacy tasks, except for phonological awareness, in which no differences were found between the groups. In addition, in the early numeracy tasks, a difference was found only in the task which included linguistic knowledge, number knowledge, and counting tasks, in which the monolingual children performed better. Furthermore, stronger correlations were found between the early numeracy and literacy skills among the monolingual group compared to the bilingual group. The study findings stress the importance of working on linguistic abilities such as vocabulary expansion in kindergarten among populations in which more than one language is spoken. Strengthening these abilities can reduce the gap between bilingual children and their monolingual classmates before entering school.